Pengaruh Filsafat Konfusianisme dalam Perubahan Kebijakan Luar Negeri Tiongkok Terhadap Isu Denuklirisasi Korea Utara - Rachmat Hidayatullah; Mohamad Rosyidin; Marten Hanura (Journal of International Relations Diponegoro, 2022)
This research provides to explain why did the Chinese Government change hisforeign policy to become more active towards North Korean denuclearization issue. Thisresearch also aims to describe the construction of Chinese foreign policy based on hisinside factors to explain the direction of Chinese foreign policy itself toward NorthKorean denuclearization. This research is using Constructivism Theory with CongruentMethod to analyze how Confucianism norms as an ancient Chinese philosophy can beinfluence on Chinese foreign policy toward this issue. The result of this research showthat the influence of Confucianism norms had been constructed to the China identity aspeace-loving country. In addition, the changing of Chinese foreign policy itself had beenseen as a positive image towards peace by the international community. The positiveimage can be used to bargain his position into international community. Based on thatresult, the changing of Chinese foreign policy can be seen from a different point of viewwhich is non-Grand IR theories and also recommend especially for IndonesiaGovernment to build a national image to show Indonesian values and norm.